Os distúrbios osteomusculares e suas consequências para os profissionais da odontologia - Freire, Ana Carolina da Graça Fagundes [UNESP] (2015)
Dentistry is a job very vulnerable to occupational risks mainly those concerning work postures. Objective: To verify the prevalence of musculoskeletal disturbs in dentists who are enrolled in post-graduation courses in many specialties, stablishing possible relation with social, demographic and occupational factors; to evaluate the professionals' perception regarding risk factors and correlation the musculoskeletal pain to the consequent incapacity among dental professionals. Method: In this cross-sectional study the professionals answered to the validated instruments: Work-related activities that may contribute to job - related pain and/or injury, Nordic Musculoskeletal Questionnaire (NMQ), Pain Disability Questionnaire (PDQ) and the Numerical Scale for Pain. Variables about social, demographic and occupational characterization were also collected. The data analysis was performed using SPSS software - version 21.0 and it was applied the Sperman's Test. To compare the groups it was applied the non-parametric Mann-Whitney and Kruskal-Walis tests. Results: of total (N=94), 90.4% reported that they have experience of musculoskeletal pain, and these dentists showed risk 13.40 times higher to feel pain in inferior part of back than those who had no symptoms. The most prevalent areas of pain were the neck (58.5%), inferior (57.4%) and superior (55.3%) parts of back, shoulders (46.8%), and fists/hands (44.7%). The relation between the existence of pain and uncomfortable occupational postures of dentists was statistically significant, e.g. to work in wrong positions or in strait locals (p-value 0.005). Total average of PDQ was 7.91; on functional condition domain (FC) ...